ELECTION, STORAGE AND IODINE SALT QUALITY IN THE FAMILY LEVEL IN TIMBULHARJO VILLAGE, SEWON DISTRICT, BANTUL REGENCY, YOGYAKARTA - laila, nurul; Waryana, Waryana; Mursyid, Abidillah (Kesmas Indonesia, 2018)
One factor of IDD (Iodine Deficiency Disorders) is the lack consumptionof iodine, eitheriodinecomes from foodorsaltthat has beenfortified withiodine. Behavior ofhousewivesin selectingandstoringsaltshould be appropriatetomaintainthe quality ofsalt. Objective of the research to determine the manner of selection, methods of storage, the quality of iodized salt, and the Differences in the quality of iodized salt by way of elections and salt storage by housewives.Type of research is observational research in the form of analytic survey with cross sectional study design. The sample was selected using proportional random sampling technique. Data were collected in May 2015 in the Mriyan Orchard by conduct home visits, with a total study population of 410 households and the number of samples used as much as 78 households. This research was analyzed using Chi-square test.The results showed differences in the quality of iodized salt by way of elections and salt storage in the Mriyan Orchard with a value of p <0.05. Based on the descriptive results, it is known that the election of salt housewife compliance (89.7%), as well as salt storage means compliance (70.5%), the quality of iodized salt in the Mriyan Orchard reach the target the use of iodized salt for all (92.3%). There is a differences in the quality of iodized salt by way of elections (p = 0.000). Then, there is a differences in the quality of iodized salt by salt storage (p = 0.003)